EPIDEMIOLOGY AND BACTERIOLOGICAL ANALYSIS OF ACUTE PHARYNGITIS AND TONSILLITIS IN PEDIATRIC PATIENTS: A STUDY FROM A TERTIARY CARE HOSPITAL - Dr. Mohd Nasaruddin (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Acute pharyngitis and tonsillitis are common infections, particularly in the pediatric population, leading to significant healthcare visits worldwide. This study aimed to analyze the incidence, clinical features, and bacteriological characteristics of acute pharyngitis and tonsillitis in children attending a tertiary care hospital. A total of 150 pediatric patients, aged 2-12 years, were included in this study. Data were collected on age, socioeconomic status, occupation, symptoms, signs, and bacterial pathogens. The highest incidence of acute pharyngitis and tonsillitis was observed in the 6-8 years age group (52%), with a higher prevalence in male patients (56%) and children from low-income families (59%). Clinical symptoms included sore throat (100%), fever (59%), and odynophagia (35%). Bacteriological analysis revealed that 76% of the samples contained pathogens, with 65% Gram-positive bacteria and 20% Gram-negative bacteria. The most common pathogen identified was Streptococcus pyogenes. These findings highlight the need for accurate diagnosis and appropriate antibiotic use, especially in pediatric patients from lower socioeconomic backgrounds, and emphasize the role of targeted treatment to prevent complications such as recurrent infections and antibiotic resistance.